Thursday

March 5, 2015

March 5, 2015

Posted by **Lea** on Monday, February 18, 2013 at 5:24pm.

a1=(-3x1)2 +4=13

a2=(-3x2)2+4-40

a3=(-3x3)2+4=85

a4=(-3x4)2+4=148

a5=(-3x4)2+4=229

a6=(-3x4)2+4=328

The first six terms of the sequence are 13, 40, 85, 148, 229, 328

I keep coming up with these answers but there is suppose to be an error somewhere.

- Albebra 2 -
**Steve**, Monday, February 18, 2013 at 5:26pmAs you wrote it before,

-3x^2+4 = -3(x^2) + 4

You have tabulated (-3x)^2 + 4, which is very different

**Answer this Question**

**Related Questions**

math - What is another way to write 3x(4+7)? A.3x4+7 B.3x4x7 C.3x4+4x7 D.(3x4)+(...

math, I think I have it now... - Is this the correct way to solve this? 5+3x4-2...

Mathematics - Study the number pattern in the table below and complete 2^3 (0x3^...

Math - 1. 3(1+4)=(3X1)+(3X4) Would this be Distributive Property

math - (2x4 + 3x3 - 4) + (3x4 - 2x3 - 8)

Math - Show why the below equation is true using the areas of rectangles: 2p+5p...

Math - Find the first five terms of the sequence for which a1=5,and an+1=3an+1. ...

trigonometry plz explain. - Which way is done correctly and why ?? Express the ...

Math - Study the number pattern in the table below and complete 2^3 (0x3^2)+(3x2...

Math - solve 3(4)^x for x=2.3 Do I do the 3x4 part first, or do I raise 4 to the...